Pegloticase in gout treatment - safety issues, latest evidence and clinical considerations. (December 2017) - Guttmann, Allison; Krasnokutsky, Svetlana; Pillinger, Michael H.; Berhanu, Adey
Gout is a common rheumatic condition, with increasing prevalence in recent decades. The mainstay of treatment for gout is oral urate-lowering therapy (ULT), typically with xanthine oxidase inhibitors (XOIs). Unfortunately, a proportion of patients have persistent gout that is refractory to ULT. Pegloticase, a recombinant pegylated uricase, has been approved by the US Food and Drug Administration for the treatment of refractory gout. However, concern has been raised regarding the risk of infusion reactions, which are now understood to be largely due to the development of antipegloticase antibodies. Discontinuation of pegloticase upon failure to lower serum urate has been shown to markedly reduce infusion reaction risk, but deprives patients of what, in many cases, is a last-resort treatment. In this manuscript, we review the rationale, mechanism of action, efficacy and safety of pegloticase. Additionally, we focus on potential strategies to reduce pegloticase immunogenicity and potentially make this important agent available to a wider group of patients requiring treatment.